1995
DOI: 10.1001/archpsyc.1995.03950190013003
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction Pathways

Abstract: Lithium remains the most widely used treatment for bipolar disorder, and this monovalent cation represents one of psychiatry's most important treatments. Despite its demonstrated efficacy in reducing both the frequency and severity of recurrent affective episodes and decades of clinical use, the molecular mechanisms underlying its therapeutic actions have not fully been elucidated. In this report, we review the exciting recent progress in the identification of key components of signal transduction pathways (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(32 citation statements)
references
References 119 publications
1
31
0
Order By: Relevance
“…sodium valproate or carbamazepine at therapeutically relevant concentrations [7]). These results add to the growing body of evidence suggesting that lithium alters gene expression in brain after chronic treatment which may be important in its action as a long-term prophylactic treatment for BD [8,9,11]. These results are also consistent with the current notion that psychotropic drug treatment may act through long-term adaptational changes in the CNS to bring about their therapeutic effects [8].…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…sodium valproate or carbamazepine at therapeutically relevant concentrations [7]). These results add to the growing body of evidence suggesting that lithium alters gene expression in brain after chronic treatment which may be important in its action as a long-term prophylactic treatment for BD [8,9,11]. These results are also consistent with the current notion that psychotropic drug treatment may act through long-term adaptational changes in the CNS to bring about their therapeutic effects [8].…”
Section: Resultssupporting
confidence: 85%
“…These latter results suggest that CNPaseII might be a target for CNS signal transduction pathways which regulate protein phosphorylation. Of further interest to this latter possibility is the extensive body of recent data which has suggested that lithium has important effects on such signal transduction pathways [9,11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Its mode of action is still not firmly established, but an effect on signal transduction pathways has been suggested. [3][4][5] According to the inositol depletion hypothesis, 6,7 lithium works by blocking inositol phosphatases within excessively stimulated neurons. This results in lower levels of myo-inositol and decreases the concentration of phosphatidylinositol, which reduce cellular responses to neurotransmitters.…”
Section: Introductionmentioning
confidence: 99%
“…1 Following the demonstration that therapeutic concentrations of Li uncompetitively inhibit inositol monophosphatase (IMPase) activity, 2 it was proposed 2,3 that this ubiquitous enzyme which regenerates intracellular free inositol is a principal therapeutic target of Li. These considerations spurred us to examine the in vitro activity of IMPase in 106 transformed lymphoblastoid cell lines derived from control subjects and bipolar disorder (BPD) patients characterized by therapeutic response to Li.…”
mentioning
confidence: 99%